Orthrozanclus elongata n. sp and the significance of sclerite-covered taxa for early trochozoan evolution - Zhao, Fangchen; Smith, Martin R.; Yin, Zongjun; Zeng, Han; Li, Guoxiang; Zhu, Maoyan (Scientific Reports, 2017)
Orthrozanclus is a shell-bearing, sclerite covered Cambrian organism of uncertain taxonomic affinity, seemingly representing an intermediate between its fellow problematica Wiwaxia and Halkieria. Attempts to group these slug-like taxa into a single 'halwaxiid' clade nevertheless present structural and evolutionary difficulties. Here we report a new species of Orthrozanclus from the early Cambrian Chengjiang Lagerstatte. The scleritome arrangement and constitution in this material corroborates the link between Orthrozanclus and Halkieria, but not with Wiwaxia-and calls into question its purported relationship with molluscs. Instead, the tripartite construction of the halkieriid scleritome finds a more compelling parallel in the camenellan tommotiids, relatives of the brachiopods and phoronids. Such a phylogenetic position would indicate the presence of a scleritome in the common ancestor of the three major trochozoan lineages, Mollusca, Annelida and Brachiozoa. On this view, the absence of fossil Ediacaran sclerites is evidence against any 'Precambrian prelude' to the explosive diversification of these phyla in the Cambrian, c. 540-530 million years ago.